Evaluation and treatment of flexor tendon and pulley injuries in athletes - Shapiro, L. M.; Kamal, R. N. (Clinics in Sports Medicine, 2020)
Flexor tendon and pulley injuries in athletes present a unique challenge to the treating clinician. An understanding of the anatomy and mechanism of injury helps the clinician appropriately diagnose and treat the injury. Treatment may become more complicated when associated with delays in diagnosis, in-season considerations, and an athlete`s desire to return to play. Two injuries involving the flexor tendon-pulley system, avulsion injuries of the flexor digitorum profundus tendon from its insertion onto the base of the distal phalanx and flexor pulley injuries, are examined in detail in this article.